PENGARUH PENGUNGKAPAN ESG (ENVIRONMENTAL, SOCIAL, AND GOVERNANCE) DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN - Nugroho, Yohanes Adi; Widodo, Agus; Cahyowati, Anik (Eksos, 2024)
The aim of this research is to look for the influence of Environmental, Social, Governance (ESG) on financial performance (ROA), the influence of Environmental, Social, Governance (EGS) on Company value (Tobin) as well as the influence of Environmental, Social, Governance (ESG) and financial performance ( ROA) on company value (Tobin). Using a sample of public companies listed on the Indonesia Stock Exchange in 2023. The sample was selected based on purposive sampling criteria and obtained a total sample of 66 companies that reported Environmental, Social, Governance (ESG) in 2023. This research also used a control variable, namely Size ( Total Assets) and Leverage. The analytical tool used is multiple regression using SPSS version 25. The research results show that there is no influence between ESG and financial performance (ROA) with a sig value. 0.264. ESG has no effect on company value (Tobin) with sig. 0.396. ESG and financial performance (ROA) have no effect on company value (Tobin) sig. 0.417 and 0.879.